THE USE OF POLYSEMY IN KOMPAS.COM NEWS HEADLINES - Mutawally, Ahmad Najib; Lestari, Vivi Ayu; Daniela, Lerissa; Juwita, Rahma; Lestarina, Anggi Purwa; Arma, Ladie Resyta; Berlina, Alya Ditha; Natalia, Inpresta (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to study polysemy in Kompas.com News Headlines (economic section) in Indonesia. The researcher tries to find the form of polysemy or the words contain polysemy in news headline. Classified it into several classification such as verbs, nouns, adverbs, and adjectives also regular or irregular form of polysemy and after that, the researcher tries to interpret the meaning of each polysemic words in the News Headlines. This research used descriptive method which is part of qualitative research to analyze the data. According to Azwar (1997: 6), in a descriptive method, the researcher analyzes and presents the fact systematically therefore it can be understood and concluded easily. There are 29 polysemic words found in Kompas.com News Headlines (economic section) with different forms and meanings.